2014
DOI: 10.2109/jcersj2.122.29
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of ferrite-silica aerogel nanocomposite

Abstract: The ferrite-silica aerogel nanocomposite prepared by a solgel process and a supercritical drying process was investigated from the point of view of new composite material. The ferrite nanoparticles were prepared by a coprecipitation method and added to tetramethylorthosilicate (TMOS) in the range of 0 to 20 mol %. The ferrite-silica wet gel was prepared from TMOS containing ferrite nanoparticles, ethanol, deionized water and NH 3 aq. as a catalyst, and replaced the liquid phase and aged in the ethanol. Then, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The analysis showed that the structure of obtained carbon material was crystalline, as indicated by the miller indices of (222), ( 220) and (200). Using the Debye-Scherrer's formula, the crystalline size of the carbon material was found to be 31.03 nm [39].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that the structure of obtained carbon material was crystalline, as indicated by the miller indices of (222), ( 220) and (200). Using the Debye-Scherrer's formula, the crystalline size of the carbon material was found to be 31.03 nm [39].…”
Section: Resultsmentioning
confidence: 99%
“…The preparation process used was the same as that previously reported [5][6][7]. Tetramethyl orthosilicate (TMOS; Tokyo Chem.…”
Section: Methodsmentioning
confidence: 99%
“…We have thus considered the preparation of a variety of functional aerogels by combining functional nanoparticles and silica aerogel. We have already reported on the preparation of a magnetic aerogel that consists of a ferrite-silica aerogel nanocomposite [5,6], and dielectric aerogels that consist of a BaTiO 3 -silica aerogel nanocomposite and a carbon-silica aerogel nanocomposite [7]. Anderson et al also reported on various composite aerogels [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have prepared a ferrite-silica aerogel nanocomposite from a mixture of silica sol and ferrite nanoparticles using a supercritical drying process. 8), 9) This magnetic aerogel could be applied to a radiowave absorber and for drug delivery.…”
Section: Introductionmentioning
confidence: 99%